2014
DOI: 10.1002/chem.201402880
|View full text |Cite
|
Sign up to set email alerts
|

Azavinylidenephosphoranes: A Class of Cyclic Push–Pull Carbenes

Abstract: The synthesis of a novel family of cyclic push-pull carbenes, namely, azavinylidene phosphoranes, is described. The methodology is based on a formal [3+2] cycloaddition between terminal alkynes and phosphine-imines followed by an oxidation/deprotonation step. Carbenes 6, obtained by simple deprotonation, exhibit typical transient carbene reactivity like the intramolecular CH insertion reaction and a pronounced ambiphilic character exemplified by [2+1] cycloaddition with electron-poor methyl acrylate. Owing to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 90 publications
(33 reference statements)
0
3
0
Order By: Relevance
“…One of our main objectives is the stabilization of electron-deficient species, and recently, a framework based on norbornene was designed to stabilize silylenes using phosphines as Lewis bases . Of special interest, we have shown that, due to the weak coordination of the phosphine ligand, phosphine-stabilized silylenes remain highly reactive.…”
mentioning
confidence: 99%
“…One of our main objectives is the stabilization of electron-deficient species, and recently, a framework based on norbornene was designed to stabilize silylenes using phosphines as Lewis bases . Of special interest, we have shown that, due to the weak coordination of the phosphine ligand, phosphine-stabilized silylenes remain highly reactive.…”
mentioning
confidence: 99%
“…The IR spectrum of 6 shows the characteristic CO‐stretching frequencies with an average value of 2016 cm −1 , which is in the range of those observed for cyclic or acyclic bent allenes (2018 and 2014 cm −1 respectively) . Therefore, phosphine/sulfoxide carbone 2 appears to be stronger electron‐donating ligand than classical NHCs (2060–2036 cm −1 ) but weaker compared to cyclic carbodiphosphoranes (2001 cm −1 ) (Figure ) …”
Section: Figurementioning
confidence: 82%
“…Rhodium-stabilized donor/acceptor carbenes as reactive intermediates have been widely applied in modern organic synthesis [14][15][16][17][18][19][20][21][22][23][24][25][26]. Among them, N-sulfonyl-1,2,3-triazole as an alternative source of carbene precursor has been used to achieve the transannulation reaction for the direct synthesis of heterocycles [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41].…”
Section: Introductionmentioning
confidence: 99%